A Study on Dynamic Stochastic General Equilibrium - ESFANDYARI, Marzieh; DAHMARDE, Nazar; KAVAND, Hossein (Journal of Advanced Research in Economics and International Business, 2014)
In order to concentrate more on estimation, unchangeable wages are defined in new punitive model to create inherent unemployment because of the mismatch between supply and demand at industry level. General equilibrium model is often applied to advanced economics. However mainly about advancing economics, partial equilibrium method is used. In this research, study on dynamic stochastic general equilibrium is our main purpose. This article considered unemployment as an excess element in New-Keynesian model for Iran's economy. Also this model is based on unchangeable wages. On the one hand the main proportion of informal employment in Iran and rise in the number of dynamic stochastic general equilibrium usages in analysis of financial policies by central banks, on the other hand faults of the models, all together lead to design dynamic stochastic general equilibrium with dual labor market based on Iran’s economic characteristics. To pursue this objective in this research, the dual labor market was divided into two groups: formal and informal. Also companies are classified according to the type of their operation and workforce recruitment. The results show that this model is able to explain Iran’s economy in general. Formal labor markets play a role as a buffer in Walrasian labor markets and in Non - Walrasian labor markets . This role is practicable by comparative model. Also this article studies formal labor markets that are procyclical.